Cognitive and Environmental Benefits of Blue-Green Infrastructure and Green Skills Training - Vranayova Zuzana; Kaposztasova Daniela; Lis Anna (Selected Scientific Papers: Journal of Civil Engineering)
As cities face escalating challenges related to urbanization, public health, and climate change, innovative solutions are needed to create resilient, sustainable urban environments. Blue-green infrastructure, which integrates green spaces and water management elements, offers significant cognitive, environmental, and social benefits. This paper explores how blue-green infrastructure, coupled with initiatives like the SECOVE project, can enhance urban resilience, promote community well-being, and reduce environmental impact. By fostering vocational training in green building skills, cities can support sustainable development, job creation, and improve quality of life for urban residents. The findings emphasize the importance of integrating ecological design with skilled labor to build urban environments that are healthier, more resilient, and aligned with sustainability goals.